Competitive Anxiety in Adolescent Athletes: A Systematic Review - Musthika Dewi Pradaningtyas; Diah Karmiyati; Zainul Anwar (CV. Creative Tugu Pena, 2026)
Optimal athletic performance is the result of a synergy between physical readiness and psychological resilience, with mental factors contributing up to 80% to an athlete's success. Adolescence is a crucial phase due to the physical and psychological transitions that increase vulnerability to competitive anxiety. This review aims to analyze the dynamics of competitive anxiety in adolescent athletes and identify influencing factors. Using a systematic review method with the PRISMA protocol, 11 selected articles from 2016-2026 were analyzed. The findings indicate that competitive anxiety is a multidimensional phenomenon (cognitive and somatic) triggered by pressured expectations, low self-efficacy, and the structure of competition. Mental toughness was identified as a key protective factor, contributing between 12.2% and 45% to reducing anxiety. Furthermore, dysregulated anxiety was significantly correlated with an increased risk of physical injury. This study concludes that the development of emotional resilience should be structurally integrated into the athlete's curriculum to reduce psychological barriers and prevent performance degradation from an early age